Numerical Conformal Mapping onto the Entire Complex Plane Bounded with Finite Straight Slit and Logarithmic Spiral Slits - Yunus, AAM; Yunus, A; Nasser, MMS (IOP Publishing Ltd, 2024)
Indexed by WOS/Scopus/ERA